Assessment of the superior photocatalytic properties of Sn2+-containing SnO2 microrods on the photodegradation of methyl orange - Jorgetto, Alexandre de Oliveira [UNESP]; Boldrin Zanoni, Maria Valnice [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (Springer Nature, 2023)
A microporous Sn2+-containing SnO2 material presenting microrod morphology and a surface area of 93.0 m2 g–1 was synthesized via a simple hydrothermal route. Sn2+ ions were detected in the interior of the material (15.8 at.%) after the corrosion of a sample through sputtering. The material’s optical properties have demonstrated the absorption of a considerable fraction of visible light up to wavelengths of 671 nm, due to the presence of Sn2+ states in the material’s band structure. The analysis of the internal crystalline structure of a single microrod was carried out with the aid of a focused ion beam microscope and indicated that the material is mesocrystalline down to nanoscale level. It was proposed that the Sn2+ ions occupy intergranular sites in the highly defective crystalline structure of the material and that Sn2+ states, as well as its relatively large surface area, are responsible for the material’s superior photoactivity. The synthesized material was tested as a photocatalyst to decompose hazardous contaminants in water. The photocatalytic performance of the material was much higher than those of commercial TiO2 and SnO2 materials, decomposing nearly all methyl orange (an azo-dye model) content in water (10 mg L–1) in 6 min under UV irradiation for a photocatalyst dose of 5.33 g L–1. The photodegradation of methyl orange was also verified under visible light.